2017
DOI: 10.1016/j.healthpol.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of evidence use in public health policy making: Results from a study across six EU countries

Abstract: HighlightsMedia attitude towards underpinning policy with evidence influences policy decision makers.Individual skills, attitudes, values of policy makers impact the extent evidence use.A solid research infrastructure is facilitating but not sufficient for evidence use.Factors that impact evidence use in policy making differ by country and policy context.Interventions connecting policy makers and researchers in the policy context seem most promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 57 publications
1
86
1
5
Order By: Relevance
“…The finding that government health policies do not recognise, emphasise, prioritise or promote PCCW raises two issues with implications for ongoing research. First, we and others [1][2][3] have demonstrated a need to promote the development of evidence-informed policies. Synthesised research showed that interactive workshops or collaboration with researchers can improve the use of research by policy-makers [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that government health policies do not recognise, emphasise, prioritise or promote PCCW raises two issues with implications for ongoing research. First, we and others [1][2][3] have demonstrated a need to promote the development of evidence-informed policies. Synthesised research showed that interactive workshops or collaboration with researchers can improve the use of research by policy-makers [4].…”
Section: Discussionmentioning
confidence: 99%
“…This research employed qualitative content analysis of government policies to assess if and how they addressed PCCW [27], an approach commonly used in other policy analyses [1][2][3]. This approach can be used to qualitatively and/or quantitatively describe explicit content in written, verbal or visual communication without any theoretical interpretation.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong leadership is crucial for successful EBPH, as leaders set the tone for organizational climate and culture [19,20,[73][74][75][76][77][78]. In turn, employees interpret the culture as what management values and supports [79].…”
Section: Discussionmentioning
confidence: 99%
“…The situation in terms of research evidence‐use in policy/practice is less clear. Helping to embed secure research findings into policy and practice has been a concern for at least as long as the concern about improved evidence itself (Lawrence, 1990), and is worldwide (Koh et al , 2010, van de Goor et al , 2017). The UK ESRC want ‘Knowledge Exchange and Impact’ embedded at the heart of all ESRC research, and they present awards to studies regarded as having outstanding impact.…”
Section: Introductionmentioning
confidence: 99%